THE U.N. ENVIRONMENT PROGRAM: DEVELOPMENT OF A LEGALLY BINDING INSTRUMENT ON MERCURY (Utah Environmental Law Review; Vol 32 No 2 (2012), 2012)
In 2009, the Governing Council of the United Nations Environment Programme (“UNEP”) agreed on the need to develop a legally binding international instrument on mercury. The Council proclaimed a need for mercury partnerships between governments to reduce “risks to human health and the environment from the release of mercury and its compounds to the environment.” The business plan of the UNEP Global Mercury Partnership (“the Partnership”) provides an outline for developing and implementing projects. It describes the scope and range of the Partnership’s activities in relation to mercurial contaminations as “constrained to mercury in the atmosphere from the point of emission to the point up to and including deposition.” Expanding the scope of the proposed coverage to releases of mercury to water and land may be necessary for developing an efficient legal instrument. Recent research in the Arctic shows reduction of environmental and human exposure to mercury in the area ultimately depends “on global action to reduce the quantities of mercury entering the environmental reservoirs in which it has accumulated over the past 150 years.”   Because the Arctic region is not directly subjected to industrial or human mercury pollution, its contamination is both an indicator and a product of the global nature of mercurial pollution. The existence of mercury contamination in the arctic “confirms the need for more concerted international action” to reduce mercury levels. Stipulated by their own unique economies, world regions largely differ in the sources of mercurial releases and efforts to regulate them. The international community urgently needs to implement a legally binding instrument that covers all sources and types of mercurial contamination. The pollution cannot be contained to local areas of release because mercury’s high mobility affects the entire bio-system. This Note explores the toxic nature of mercury and its aggressive biochemical cycling that affirms the worldwide pervasiveness of mercurial contamination. The United Nations remains the leading force in establishing safety standards for producing and handling mercury. So far, the UNEP is the only global association that aims to consolidate international regulation endeavors. However, despite its highly relevant proposals, the Partnership will not be effective long-term because it does not attempt to cover water and land releases of mercury that have been traditionally dealt with locally. The potential for dangerous consequences of persistent mercurial presence in the eco-system demands a more concentrated global reporting system and comprehensive approach in developing a legally binding instrument. Due to the highly detrimental and pervasive nature of mercurial effluence, the international community should be summoned to coordinate and amplify its efforts to confine every source of mercury released into the environment.